Gamma-glutamyl transferases: a structural, mechanistic and physiological perspective - Balakrishna, Sharath; Prabhune, Asmita (Frontiers in Biology, 2013)
Gamma glutamyl transferases (GGT) are highly conserved enzymes that occur from bacteria to humans. They remove terminal γ-glutamyl residue from peptides and amides. GGTs play an important role in the homeostasis of glutathione (a major cellular antioxidant) and in the detoxification of xenobiotics in mammals. They are implicated in diseases like diabetes, inflammation, neurodegenerative diseases and cardiovascular diseases. The physiological role of GGTs in bacteria is still unclear. Nothing is known about the basis for the strong conservation of the enzyme across the living system. The review focuses on the enzyme’s physiology, chemistry and structural properties of the enzyme with emphasis on the evolutionary relationships. The available data indicate that the members of the GGT family share common structural features but are functionally heterogenous.